A hundred thousand welcomes - Donovan, Mary Lee (Greenwillow Books, an imprint of HarperCollinsPublishers, 2021)
Introduces scenes of hospitality and the word for "welcome" in more than twelve languages and cultures. Includes a pronunciation guide and information about the languages featured in the book.